2016
DOI: 10.21511/imfi.13(3-1).2016.13
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between perceived organizational support and organizational commitment among academics: the mediating effect of job satisfaction

Abstract: (2016). The relationship between perceived organizational support and organizational commitment among academics: the mediating effect of job satisfaction. Investment Management and Financial Innovations, 13(3-1), 267-273. doi:10.21511/imfi.13(3-1 The relationship between perceived organizational support and organizational commitment among academics: the mediating effect of job satisfaction AbstractThis study investigated the relationship between perceived organizational support (POS), job satisfaction (JS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 10 publications
(12 reference statements)
4
11
0
Order By: Relevance
“…Additionally, we did not find a relationship between organizational support and continuous organizational commitment (Table III). Consistent to our results, Donald et al (2016) also did not find associations between POS and continuous commitment among academics. This shows that employee's continuous commitment is not influenced by support of the organization.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, we did not find a relationship between organizational support and continuous organizational commitment (Table III). Consistent to our results, Donald et al (2016) also did not find associations between POS and continuous commitment among academics. This shows that employee's continuous commitment is not influenced by support of the organization.…”
Section: Discussionsupporting
confidence: 90%
“…A study conducted among 302 academic staff members from a South African higher learning institution also revealed a positive relationship between POS and employee organisational commitment. The researchers are of the opinion that as employees perceive enough support from their employer, they become more committed to the organisation (Batt & Colvin, 2011;Chuebang & Boatham, 2011;Mabasa et al, 2016;Ucar & Otten, 2010).…”
Section: Hypothesismentioning
confidence: 99%
“…According to Rhoades and Eisenberger (2002), the turnover-POS relationship is anchored on the fact that employees' high POS levels develop feelings of attachment to the organisation characterised by an enhanced sense of control, purpose and meaning as they perform their roles. When employees feel that the organisation appreciates them by caring about their well-being, they are likely to develop some strong feelings of commitment which reduce turnover intention (Foong-Ming, 2008;Mabasa, Ngirande, & Shambare, 2016;Tsui, Pearce, Porter, & Tripoli, 1997;Tumwesigye, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 'Input' is the student, 'Process' is the teacher and 'Output' is qualified work as a citizen which is given to the society by shaping a student and fulfilling societal needs with the significant contribution and genuine commitment of the teacher [7]. Faculty can play a crucial role in molding, refining, and modifying intellectual capacity; addressing the value, and sharing knowledge for the better future of their students [8]. Therefore, the turnover of experienced faculty may have negative effects on the organization and other faculty members.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an assessment of the motivational factors of the faculty for assuming assigned roles is most important to reduce faculty turnover, and shortages [10]. Donald et al [8] found that satisfaction with the job had a mediating effect on the relationship between perceived organizational support and AOC among academic staff at higher education institutions. Likewise, other evidence showed a significant positive association between job satisfaction and AOC in a cross-national study of employees in the United States [13], library and information professionals in Nigeria [14], primary school teachers in Ethiopia [15], and Libya [16], an oil refining Company in Iran [17] and company managers in Indonesia [18].…”
Section: Introductionmentioning
confidence: 99%